Análisis De La Fuerza Explosiva En El Golpe De Balón Con El Pie En Futbolistas Categoría Senior.Estudio De Caso: Test De Potencia De Balón - Orlando David Mazón Moreno; Jorge Giovanny Tocto Lobato; Edwin Ramiro Sánchez Guevara; Danny Javier Robalino Cárdenas (European Scientific Journal, ESJ, 2017)
The objective of the present study is to research the incidence of explosive strength on the ball kick in soccer players of senior category from the “Universidad Nacional de Chimborazo”, through the application of a comprehensive training program to improve explosive strength and ball kick for 8 weeks. In this study 50 soccer players were evaluated. The age, body weight (kg), height (cm) and body mass index were evaluated. The pre-post ball kick power test was applied as well. The soccer sketch 2.5.0 program was used for the preparation of the training sessions and the SPSS statistical package was used for the results tabulation. The results obtained are as follows: average age of 21.82, average body mass index 26.72 (kg/m2). An average of (55.92m) was obtained in the pre-test of ball strength, and an average of (62.88m) was obtained in the post test obtaining a level of significance of (0.002). In conclusion, the application of training sessions of comprehensive exercises of explosive strength and ball kick are very important to improve sports performance of the soccer players.